Aplikasi Minyak Serai Wangi Sebagai Bioaditif Bahan Bakar Pertalite - Muhammad Rafi Rasyfillah; M. Vurqon Alfarizi; Nurul Widji Triana (Universitas Islam Raden Rahmat, Malang, 2024)
Bioadditives are materials to improve the quality of fuel derived from plants. One that has the potential to be used as a bioadditive is citronella oil. Citronella oil can be obtained by several methods, one of which is using the water and steam distillation method. This distillation process is carried out with 1 kg of citronella, 3 liters of water, 100 °C operating temperature, and 2 hours of distillation time. Based on the GC-MS test, citronella oil contains 19.35% geraniol, 1.24% citronellal, and 1.72% citronellol. The mixing ratio is 2:1000; 4:1000; 6:1000; 8:1000; 10:1000 ml, and the stirring time is 1; 2; 3; 4; 5 minutes. This study aims to increase the octane number, calorific value, density, and viscosity of pertalite fuel. The best test results were obtained at 10:1000 ml and 5 minutes, with a calorific value increase of 7.35% and an octane number increase of 2.97%.